2014
DOI: 10.1111/eip.12207
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and acceptability of cognitive adaptation training for first‐episode psychosis

Abstract: This study provides evidence that CAT is a highly feasible and acceptable intervention in FEP, which may be easily integrated within existing services. The effectiveness of CAT in improving functional outcomes in FEP is worthy of investigation in a larger trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…For such individuals with early persistent deficits, interventions that involve both adaptive or compensatory cognitive strategies as well as directly addressing functional recovery, such as supported education or employment may be especially effective. Indeed, a small pilot study of cognitive adaptation therapy (CAT) for FEP patients found that this type of intervention was both highly feasible and acceptable, with case managers reporting that their patients benefited from working with a CAT therapist and that CAT enhanced their treatment [85 ].…”
Section: Implications For Interventionmentioning
confidence: 99%
“…For such individuals with early persistent deficits, interventions that involve both adaptive or compensatory cognitive strategies as well as directly addressing functional recovery, such as supported education or employment may be especially effective. Indeed, a small pilot study of cognitive adaptation therapy (CAT) for FEP patients found that this type of intervention was both highly feasible and acceptable, with case managers reporting that their patients benefited from working with a CAT therapist and that CAT enhanced their treatment [85 ].…”
Section: Implications For Interventionmentioning
confidence: 99%
“…Studies of cognitive training interventions in pre-psychotic illness remain limited. One study has demonstrated acceptability and feasibility of a compensatory-based approach (Cognitive Adaptive Training) in early illness phase (34); however, the small sample size (n = 5), individual format, and lengthy duration undermined its widespread application in real-world settings. Although preliminary evidence suggests computerized drill-andpractice as a feasible intervention with potential cognitive benefits for CHR (66), controlled studies are not yet published.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive intervention trials (i.e., cognitive remediation or cognitive training) in individuals meeting CHR or early psychosis criteria remain limited and have produced mixed findings (33); although improvements in cognitive outcomes have been noted in some cognitive domains, these cognitive gains do not always generalize to improvements in community functioning. Although pro-cognitive interventions in pre-and early illness stages appear promising, preliminary evidence suggests that a compensatory strategy approach may best target areas of cognition typically impaired in early psychosis (34).…”
Section: Introductionmentioning
confidence: 99%
“…Common symptoms of SMI include cognitive impairments, which include difficulties with memory and in initiating activities . One way to overcome such problems could be by using cognitive adaptation training (CAT), which is a psychosocial intervention proven useful for persons with SMI . Altogether, cognitive and emotional symptoms may affect the capacity to engage effectively in lifestyle habits .…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] One way to overcome such problems could be by using cognitive adaptation training (CAT), which is a psychosocial intervention proven useful for persons with SMI. 11,12 Altogether, cognitive and emotional symptoms may affect the capacity to engage effectively in lifestyle habits. [13][14][15] Other factors that could obstruct healthy lifestyle habits within this group include a deficient knowledge of the benefits of living a healthier life, 16 and a lack of support from the staff, which can manifest as negative attitudes.…”
Section: Introductionmentioning
confidence: 99%